Three times greater weight of daytime than of night‐time temperature on leaf unfolding phenology in temperate trees. Issue 3 (4th July 2016) - Fu, Yongshuo H.; Liu, Yongjie; De Boeck, Hans J.; Menzel, Annette; Nijs, Ivan; Peaucelle, Marc; Peñuelas, Josep; Piao, Shilong; Janssens, Ivan A.
Summary: The phenology of spring leaf unfolding plays a key role in the structure and functioning of ecosystems. The classical concept of heat requirement (growing degree days) for leaf unfolding was developed hundreds of years ago, but this model does not include the recently reported greater importance of daytime than night‐time temperature. A manipulative experiment on daytime vs night‐time warming with saplings of three species of temperate deciduous trees was conducted and a Bayesian method was applied to explore the different effects of daytime and night‐time temperatures on spring phenology. We found that both daytime and night‐time warming significantly advanced leaf unfolding, but the sensitivities to increased daytime and night‐time temperatures differed significantly. Trees were most sensitive to daytime warming (7.4 ± 0.9, 4.8 ± 0.3 and 4.8 ± 0.2 d advancement per degree Celsius warming (d °C −1 ) for birch, oak and beech, respectively) and least sensitive to night‐time warming (5.5 ± 0.9, 3.3 ± 0.3 and 2.1 ± 0.9 d °C −1 ). Interestingly, a Bayesian analysis found that the impact of daytime temperature on leaf unfolding was approximately three times higher than that of night‐time temperatures. Night‐time global temperature is increasing faster than daytime temperature, so model projections of future spring phenology should incorporate the effects of these different temperatures.